2007
DOI: 10.1902/jop.2007.060481
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reported Periodontal Disease: Validation in an Epidemiological Survey

Abstract: These analyses suggest that self-report may be valid for surveillance of periodontal disease burden and trends in the American population, in lieu of more costly clinical periodontal examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
90
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(106 citation statements)
references
References 30 publications
14
90
0
2
Order By: Relevance
“…The prevalence of severe periodontitis in the US ranges from 16% to 32% among adults of 40-50 years of age and from 31% to 39% among adults of more than 65 years of age [16,17]. Every year 100 million dental plain radiographies are perfomed in the US, with a radiation dose of 0.005-0.01 mSv per radiography [18].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of severe periodontitis in the US ranges from 16% to 32% among adults of 40-50 years of age and from 31% to 39% among adults of more than 65 years of age [16,17]. Every year 100 million dental plain radiographies are perfomed in the US, with a radiation dose of 0.005-0.01 mSv per radiography [18].…”
Section: Discussionmentioning
confidence: 99%
“…Self-report measures have been shown to provide accurate estimates for number of teeth (7, 8, 1216), periodontal disease (17, 18), dental fillings (8) and the presence of dentures or prosthetic appliances (8, 12, 14, 16, 19). Self-report measures, however, have not always been found to accurately reflect the number of replaced teeth (19), periodontal disease (8, 20, 21) or dental agenesis (22).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the variables identified in other studies of self‐reported periodontitis, Taylor and Borgnakke, found that age, sex, race, smoking and questions about periodontal health were predictors of periodontitis. Similarly, in our study, age and (marginally) poor oral health were associated with the presence of periodontitis.…”
Section: Discussionmentioning
confidence: 90%